Biting midges (Diptera: Ceratopogonidae) as putative vectors of zoonotic Onchocerca lupi (Nematoda: Onchocercidae) in northern Arizona and New Mexico, southwestern United States - Roe, Chandler C.; Holiday, Olivia; Upshaw-Bia, Kelly; Benally, Gaven; Williamson, Charles H. D.; Urbanz, Jennifer; Verocai, Guilherme G.; Ridenour, Chase L.; Nottingham, Roxanne; Ford, Morgan A.; Lake, Derek P.; Kennedy, Theodore A.; et al. (Frontiers in Veterinary Science, 2023)
Onchocerca lupi (Rodonaja, 1967) is an understudied, vector-borne, filarioid nematode that causes ocular onchocercosis in dogs, cats, coyotes, wolves, and is also capable of infecting humans. Onchocercosis in dogs has been reported with increasing incidence worldwide. However, despite the growing number of reports describing canine O. lupi cases as well as zoonotic infections globally, the disease prevalence in endemic areas and vector species of this parasite remains largely unknown. Here, our study aimed to identify the occurrence of O. lupi infected dogs in northern Arizona and New Mexico, United States (US). We then used these results to perform targeted insect trapping to identify the vector of this nematode. A total of 532 skin samples from randomly selected companion animals with known geographic locations within the Navajo Reservation were collected and molecularly surveyed with PCR for the presence of O. lupi DNA (September 2019 – June 2022) using previously published nematode primers (COI) and DNA sequencing. O. lupi DNA was detected in 50 (9.4%) sampled animals throughout the reservation. Using positive animal samples to target geographic locations, pointed hematophagous insect trapping was performed to identify potential O. lupi vectors. Out of 1,922 insects screened, 35 individual insects and 19 insect pools tested positive for the presence of O. lupi, all of which belong in the Diptera family. This increased surveillance of definitive host and biological vector/intermediate host is the first large scale prevalence study of O, lupi in companion animals in an endemic area of the US and identified an overall prevalence of 9.4% in companion animals as well as multiple likely biological vector and putative vector species in the southwestern United States. Furthermore, the identification of these putative vectors in close proximity to human populations coupled with multiple, local zoonotic cases highlight the One Health importance of O. lupi.